Realising radical potential: building community power in primary health care through Participatory Action Research - Denny Mabetha; Temitope Ojewola; Maria van der Merwe; Reflect Mabika; Gerhard Goosen; Jerry Sigudla; Jennifer Hove; Sophie Witter; Lucia D'Ambruoso; On behalf in collab the Verbal Autopsy with Participatory Action Research (VAPAR) (BMC, 2023)
Abstract Background While community participation is an established pro-equity approach in Primary Health Care (PHC), it can take many forms, and the central category of power is under-theorised. The objectives were to (a) conduct theory-informed analysis of community power-building in PHC in a setting of structural deprivation and (b) develop practical guidance to support participation as a sustainable PHC component. Methods Stakeholders representing rural communities, government departments and non-governmental organisations engaged through a participatory action research (PAR) process in a rural sub-district in South Africa. Three reiterative cycles of evidence generation, analysis, action, and reflection were progressed. Local health concerns were raised and framed by community stakeholders, who generated new data and evidence with researchers. Dialogue was then initiated between communities and the authorities, with local action plans coproduced, implemented, and monitored. Throughout, efforts were made to shift and share power, and to adapt the process to improve practical, local relevance. We analysed participant and researcher reflections, project documents, and other project data using power-building and power-limiting frameworks. Results Co-constructing evidence among community stakeholders in safe spaces for dialogue and cooperative action-learning built collective capabilities. The authorities embraced the platform as a space to safely engage with communities and the process was taken up in the district health system. Responding to COVID-19, the process was collectively re-designed to include a training package for community health workers (CHWs) in rapid PAR. New skills and competencies, new community and facility-based alliances and explicit recognition of CHW roles, value, and contribution at higher levels of the system were reported following the adaptations. The process was subsequently scaled across the sub-district. Conclusions Community power-building in rural PHC was multidimensional, non-linear, and deeply relational. Collective mindsets and capabilities for joint action and learning were built through a pragmatic, cooperative, adaptive process, creating spaces where people could produce and use evidence to make decisions. Impacts were seen in demand for implementation outside the study setting. We offer a practice framework to expand community power in PHC: (1) prioritising community capability-building, (2) navigating social and institutional contexts, and (3) developing and sustaining authentic learning spaces.